An Anthropology of the Contemporary in France. Issue 3 (1st December 2019) - Ingram, Mark
Abstract : Cultural anthropology in France continues to bear the influence of a colonial-era distinction between "modern" societies with a high degree of social differentiation (and marked by rapid social change) and ostensibly socially homogeneous and change-resistant "traditional" ones. The history of key institutions (museums and research institutes) bears witness to this, as does recent scholarship centered on "the contemporary" that reworks earlier models and concepts and applies them to a world increasingly marked by transnational circulation and globalization. Anthropology at the Crossroads describes the evolution of a national tradition of scholarship, changes to its institutional status, and the models, concepts, and critical perspectives of anthropologists currently revisiting and reworking the foundations of the discipline in France.